Income Analysis of Usahatani in Cempi Jaya Village, Hu'u Sub-District, Dompu District - Ihsan Abdillah; Iwan Harsono; Baiq. Saripta Wijimulawiani; B. Vineshkumar (Tinta Emas Publisher, 2024)
This study aims to analyze the effect of the number of dependents, labor, land area and costs on farm income in Cempi Jaya Village, Hu'u Sub-district, Dompu Regency. The type of research used in this study is quantitative research. The population was 356 farmers with a sample of 78 farmers in Cempi Jaya Village. The data collection methods used were interviews, documentation and questionnaires. The types of data used in this study are primary data and secondary data. The data was processed using the SPSS 27 application using the multiple linear regression method. Based on the analysis conducted in this study, the results show that the variable number of dependents, labor and land area has no significant effect on corn farm income, while the cost variable has a significant effect on corn farm income.